ANALISIS NILAI BUDAYA DALAM SEDEKAH BUMI DI DESA TEGOWANU WETAN, KECAMATAN TEGOWANU KABUPATEN GROBOGAN - Tyas Pitaloka; Wasino; Arghita Aricindy; Tri Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the culture values contained in the earth alms tradition in Tegowanu Village, Tegowany District, Grobogan Regency. This research uses a descriptive qualitative method, employing data collection techniques such as interviews and library research (i.e. reading and taking notes from books or journals). Tegowanu has a sedekah bumi tradition that is held once a year in the “Bulan Apit” (in the Javanese calendar) and the month of Dzulqo’dah (in the Hijri calendar). The execution of this sedekah bumi tradition consists of: bathing (penjamasan) sacred heirloom objects, ambengan (communal meal), and a shadow puppetry performance. The findings showa that the sedekah bumi tradition actually holds deeply embedded cultural values, such as: local wisdom, mutual cooperation (gotong royong), tolerance, togetherness among residents, and social care.